PROCESS VALIDATION OF BETA-SITOSTEROL HAIR GEL FORMULATION AND EVALUATION OF 5 ALPHA REDUCTASE INHIBITION IN VITRO FOR THE TREATMENT OF ANDROGENETIC ALOPECIA - CHAKRABORTY, ARPAN; BHATTACHARJEE, ARKA; CHAKRABORTY, MANAS; MUKHOPADHYAY, GOUTAM (International Journal of Applied Pharmaceutics, 2023)
Objective: The present study was aimed to develop topical gel containing β-sitosterol using carbopol 940 as a gelling agent and to investigate 5 alpha reductase (5α-reductase) inhibitory activity of suitable gel formulation and compare it with a commercial product used topically for alopecia. Methods: Three different batches of β-sitosterol hair gel formulation were manufactured and evaluated. Additionally, the 5α-reductase inhibitory activity of the prepared formulation, finasteride as a positive control, was evaluated and compared to the commercial herbal formulation used. Results: According to the analytical findings of three different batches, the gel formulation is good in appearance, homogeneous, and easily spreadable. Based on findings from HPLC and HPTLC, the amount of β-sitosterol in those formulations complies with the label claim. By checking different critical parameters of those batches, we established the manufacturing process method validation and the process reproducibility. In vitro results showed the good 5α-reductase inhibitory potential of prepared gel formulation and then commercial product. The IC50 value of the prepared formulation was 118.960±0.634 (µg/ml) and standard beta-sitosterol 88.854±0.70 (µg/ml), whereas Finasteride (positive control) 224.372±3.103 (ng/ml). Conclusion: Thus, β-sitosterol formulation utilises a straightforward, low-cost production, less time-consuming process with minimal facility and equipment requirements. The formulation may be a promising candidate for future investigation into their antiandrogenic activities.